Agriculture, development, and the global trading system: 2000-2015 - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2017)
This book is devoted to the complex relationship between the global trading system and food security, focusing on two important elements: the Doha Development Agenda (DDA) and how food price volatility can be managed, or not, through trade instruments. The first section of the book is based on the premise that more trade integration can fight poverty and alleviate hunger. The second section examines whether managing price volatility is doable through more or less trade integration. This section deals in particular with policy instruments available for policy makers to cope with price volatility: food stocks, crop insurance, and export restrictions. Analysis concludes that without a strong and efficient World Trade Organization (WTO) capable of conducting ambitious trade negotiations, the food security target will be much more difficult to hit.